Application of the Think Talk Write Model in Teaching Writing Skills: A Field Study at Senior High School: تطبيق نموذج "Think Talk Write" في تعليم مهارة الكتابة : دراسة ميدانية في المدرسة الثانوية - Vira Hilma Fadhila; Zuhdi Zainul Muttaqin; Nabella Dwi Maharani; Januar Yunamto (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2026)
The writing skills of eighth-grade students at MTs Negeri Ngargoyoso are still relatively low, as indicated by students' difficulties in expressing ideas in written form, constructing Arabic sentences correctly, and their limited vocabulary mastery to support the writing process. This study employed a descriptive qualitative method and was conducted from January to February of the 2025/2026 academic year at MTs Negeri Ngargoyoso. The research subjects consisted of an Arabic language teacher and eighth-grade students. Data were collected through observation, interviews, and documentation, and then analyzed through data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation and technique triangulation. The findings reveal that the Think Talk Write model was implemented through three stages: thinking (think), discussing (talk), and writing (write). In the thinking stage, students read and independently took notes on the material; subsequently, they discussed the material in groups to exchange understanding and finally expressed the results of their discussions and comprehension in written form during the writing stage. This study contributes to the development of Arabic language learning that emphasizes students' active participation and engagement, particularly in improving writing skills. The findings also indicate that the Think Talk Write learning model is a viable and effective alternative for teaching Arabic at Islamic junior high schools (Madrasah Tsanawiyah) and other equivalent educational institutions.